DISTRIBUTION MOVEMENT OF ORIGIN DESTINATION OF GOODS TRANSPORTATION VEHICLE TRANSPORT (CASE STUDY OF JALAN KHATULISTIWA, UPPKB SIANTAN WEIGHT BRIDGE, PONTIANAK) - Kadarini, S. Nurlaily; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2024)
This case study investigates the distribution patterns of goods transport vehicles on Jalan Khatulistiwa, focusing on the UPPKB Siantan weighbridge in Pontianak. Urban centers are crucial in goods distribution and act as nodes connecting hinterland areas. Urban sprawl necessitates longer commutes as cities grow and exacerbates peak-hour traffic congestion. Identifying and understanding movement patterns using Origin-Destination Matrices (ODM) is essential for optimizing transportation policies and economic development.The study employs a mixed-method approach to collect primary data through field surveys, mapping the movement of goods and transport vehicles from origin to destination. Given their significance in urban freight movement, land transportation and hefty vehicle traffic is the primary focus. The analysis includes delineating Origin-Destination Matrices (ODMs) to assess traffic flows and identify critical routes and distribution nodes. Insights from this study inform transportation planning strategies to enhance efficiency, reliability, and sustainability of goods movement within Pontianak.Through detailed data collection and analysis, this research aims to contribute practical insights for policymakers and urban planners to improve traffic management and enhance the overall transportation network's performance in Pontianak, ultimately supporting economic growth and development.